1998
DOI: 10.1577/1548-8446(1998)023<0006:mmtifg>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Managing Macrophytes to Improve Fish Growth: A Multi-lake Experiment

Abstract: Macrophyte harvesting often has been suggested as a way to improve fish growth and size structure in lakes with high densities of submergent macrophytes and stunted fish populations. However, previous experimental tests have provided no clear consensus on whether the technique works for management. We conducted a series of whole‐lake manipulations to test the effects of macrophyte removal on growth of bluegill and largemouth bass. We selected four lakes in southern and central Wisconsin for experimental manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
63
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 40 publications
0
63
1
Order By: Relevance
“…Piscivores often use complex habitats for foraging and ambush opportunities (Ekl€ ov 1997;Olson et al 1998;Sass et al 2006a). In addition to Muskellunge, other fishes are also attracted to CWH and their abundance may increase with CWH structural complexity (Newbrey et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Piscivores often use complex habitats for foraging and ambush opportunities (Ekl€ ov 1997;Olson et al 1998;Sass et al 2006a). In addition to Muskellunge, other fishes are also attracted to CWH and their abundance may increase with CWH structural complexity (Newbrey et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Fish and shrimps seemed to be the food alternatives of pike and largemouth bass based on their abundance and vulnerability which vary seasonally. M. salmoides are less efficient foragers than E. lucius in areas that are thick with hydrophytes that provide refuge for the fish prey (OLSON et al, 1998) and its foraging success has been shown to decrease with the increasing abundance of submerged vegetation (GODINHO et al, 1997). In manipulative experiments in a Texas reservoir BETTOLLI et al (1992) have found that before aquatic vegetation removal the diet of largemouth bass was made mainly of insects, amphipods and P. antennarius, whereas after the removal of the vegetation piscivory increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The open water area adjacent to dense hydrilla habitat at Sandmine Lake was approximately 1 ha, and was not large enough to influence DO on dense hydrilla bed edges or interior. Increasing ecotonal habitat via channelization can promote macroinvertebrate and fish communities with increased hydrilla branching and fish foraging, provide alternative fish habitat during hypoxic periods, and benefit recreational boaters for navigation (Lillie & Budd 1992;Trebitz & Nibbelink 1996;Olson et al 1998). With recent advances in GPS and deep-water mechanical removal of dense macrophytes, longer term control in channels may now be possible (Haller & Jones 2012).…”
Section: Discussionmentioning
confidence: 99%